Chemical Composition, Antioxidant and Hypoglycemic Activities of Phenolic Fractions from Sargassum pallidum - XIE Xing, WANG Siyu, WANG Peixin, ZHANG Lu, TU Zongcai, CHEN Chun, FU Xiong (Shipin Kexue, 2023)
Three forms of soluble phenolics, free phenolics (FP), esterified-bound phenolics (EP) and glycoside-bound phenolics (GP), were extracted from Sargassum pallidum, and their chemical composition was identified by ultra-high performance liquid chromatography-quadrupole-time of flight-tandem mass spectrometry (UPLC-QTOF-MS/MS). Their antioxidant and α-glucosidase inhibitory activities in vitro were evaluated. Results demonstrated that the soluble phenolics in S. pallidum mainly existed in a bound form, GP and EP fractions contained the highest contents of total phenolics (68.30 mg/g) and flavonoids (83.49 mg/g), respectively. A total of 22 compounds were identified in the three phenolic fractions, including three simple phenolics, four flavonoids and two phenolic acids. Biological activity tests indicated GP had the highest cellular antioxidant activity (CAA value = 18.18 μmol/g), 1,1-dipheny1-2-picrylhydrazyl (DPPH) radical scavenging activity (IC50 = 84.6 μg/mL) and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation scavenging activity (IC50 = 127.01 μg/mL), while EP had the strongest oxygen radical absorbance capacity (5 322.85 μmol/g) and α-glucosidase inhibitory activity with IC50 value of 27.09 μg/mL. The hypoglycemic activity of EP was significantly higher than that of acarbose. Inhibition kinetics analysis showed that the inhibition mode of α-glucosidase by the three phenolic fractions was a mixed type. In conclusion, bound phenolics from Sargassum pallidum have excellent antioxidant and α-glucosidase inhibitory activities, which will provide a scientific basis for the development of natural antioxidants and hypoglycemic foods.